Retraction Notice "The Challenges of Impementation of Developing A Tod Area in Thessaloni-ki, Greece" - Sasmit, Anjar; Riyanti, Nova (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
RETRACTION TO: Sasmit, A., & Riyanti, N. (2023). The Challenges of Impementation of Developing A Tod Area in Thessaloni-ki, Greece. International Journal of Multidisciplinary: Applied Business and Education Research, 4(8), 2765-2774. https://doi.org/10.11594/ijmaber.04.08.16 . This article has been retracted by the publisher to be in violation of IJMABER Publication Ethics. IJMABER requires authors to declare that their work is original and has not been published or considered by another journal. This article is a serious misuse of scientific publishing. The scientific community strongly disapproves of this, and the journal apologizes to readers for not catching it during submission. The presenting author of this paper has the option to appeal this decision by contacting editor.ijmaber@futuresciencepress.com.